Crystal growth and scintillation properties of Tm3+ doped LaCl3 single crystal for radiation detection. (November 2022) - Tariwong, Y.; Vuong, P.Q.; Luan, N.T.; Saha, Sudipta; Kim, H.J.; Wantana, N.; Chanthima, N.; Kaewkhao, J.; Kothan, S.
Abstract: Single crystal of Tm-doped LaCl3 (LaCl3 :Tm 3+ ) with the dimension of diameter 7 mm and length 55 mm was successfully grown using an in-house-developed Bridgman furnace. The grown crystal has the self-trapped exciton (STE) emission in the range of 300–500 nm along with the characteristic emissions corresponding to the 4f-4f transition of Tm 3+ ions under X-ray excitation. The scintillation characterizations of the grown crystal were performed by pulse height spectra, scintillation decay time, as well as pulse shape discrimination studies under γ-ray and α-particle excitation sources. The LaCl3 :Tm 3+ crystal was found to have a high light yield (42, 000 ± 4, 200 ph/MeV) with 4.2% energy resolution under γ-rays excitation. Moreover, the pulse shape discrimination was studied using 137 Cs and 241 Am as the radiation sources with a good FOM value. The results conclude the LaCl3 :Tm 3+ single crystal to be a promising candidate for X-ray and γ-ray detection purposes. Highlights: The LaCl3 :Tm 3+ crystal was successfully grown by Bridgman technique. Host STE band and characteristic Tm 3+ transition are visible in the XIL studies. High light yield (41, 511 ± 2, 906 ph/MeV) with 4.23% energy resolution ( 137 Cs source). The timing performance of crystal was found to be 3.42 μs (89%) with 137 Cs source. The excellent PSD capability of LaCl3 :Tm 3+ crystal between γ-ray and α-particles.